2022
DOI: 10.1136/ijgc-2022-004004
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and integrative oncology for taxane-induced peripheral neuropathy: a randomized multicentered study

Abstract: ObjectiveTo compare the effectiveness of acupuncture alone or with additional integrative oncology modalities for taxane-induced peripheral neuropathy-related symptoms in patients with gynecological and breast cancer.MethodsThe study was a prospective evaluation of patients undergoing twice-weekly treatments with either acupuncture alone (single-modality, group A) or with additional manual-movement and mind-body therapies (multimodality, group B), for 6 weeks. Symptom severity was assessed at baseline, 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In recent years, research on CAT for the treatment of NP has increased year by year, with a proliferation of systematic reviews, large-sample randomized controlled trials, and original studies. [31][32][33][34] However, bibliometric analyses of the disciplinary structure, status of study, and hotspots in the area are still vacant. Therefore, in this study, we summarized the general information of this research field by bibliometrics, and analyzed the contributions and collaborations of countries, institutions, and authors to the field.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on CAT for the treatment of NP has increased year by year, with a proliferation of systematic reviews, large-sample randomized controlled trials, and original studies. [31][32][33][34] However, bibliometric analyses of the disciplinary structure, status of study, and hotspots in the area are still vacant. Therefore, in this study, we summarized the general information of this research field by bibliometrics, and analyzed the contributions and collaborations of countries, institutions, and authors to the field.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on acupuncture focus on finding areas for its clinical application. There are clinical trials researching the usage of acupuncture in perioperative and postoperative treatment [98,104,105], chronic pain management [106], depression [107], irritable bowel syndrome [108], fibromyalgia [109], rheumatoid arthritis [98], neuropathy [110,111]. A study on 107 patients showed that the group of patients who received epidural analgesia and acupuncture reported significantly better pain management scoring low on pain scales (postoperatively on the day of operation and two days after) than the control group who received epidural analgesia only [98,104].…”
Section: Acupuncturementioning
confidence: 99%
“…The strength of recommendation for acupuncture for patients with chemotherapy-induced peripheral neuropathy and patients undergoing cancer surgery or other invasive procedures is weak [116]. Nevertheless, some studies reported that acupuncture reduces taxane-induced peripheral neuropathy (tingling, numbness, pain in distal extremities) and overall well-being [110,111].…”
Section: Acupuncturementioning
confidence: 99%
“…Small sample study suggests that the effect of AC on chemotherapy‐induced peripheral neuropathy is uncertain 159 . However, studies have shown that AC can improve chemotherapy‐induced peripheral neuropathy 51–57,160 and reduce the use of analgesics 58 . AC may reduce the incidence of high‐grade peripheral neuropathy during chemotherapy and improve its symptoms, with a potential long‐term effect 59,60 .…”
Section: Clinical Applications Of Acupuncture In Cancer Therapymentioning
confidence: 99%